Association of ARNT splice variants with estrogen receptor-negative breast cancer, poor induction of vascular endothelial growth factor under hypoxia, and poor prognosis - Qin, C; Wilson, C; Blancher, C; Taylor, M; Safe, S; Harris, A L (Clinical cancer research, 2001)
The aryl hydrocarbon receptor nuclear translocator (ARNT) is a basic helix-loop-helix transcription factor that forms heterodimers with the aryl hydrocarbon receptor (AhR) or hypoxia inducible factor-1alpha to activate transcription via xenobiotic response element or hypoxia response element, respectively. Thus, it plays a major role in two key biochemical pathways involved in tumor growth. We previously showed that estrogen receptor (ER)-negative breast cancer cell lines expressed a splice variant of ARNT that was associated with Ah nonresponsiveness. We have now used a sensitive PCR method to analyze the expression of the variant in a series of 92 breast cancers to assess interactions with the ER and prognosis. The splice variant could be detected in all of the cases examined, with high ratios of variant:full-length ARNT (> or =10) characterized in 10 cases. When the patient group was split into quartiles by increasing splice variant ratios, there was an inverse relationship of ER status to ARNT splice-variant ratios (P = 0.01, chi(2)). Univariate analysis showed that cases with high ARNT splice-variant ratios > or =10 had a worse relapse-free and overall survival (P > or = 0.03; hazard ratio, 2.7; and P = 0.006; hazard ratio, 3.9, respectively). In multivariate analysis for relapse-free and overall survival, ARNT splice-variant ratio was the strongest independent factor and, although inversely related to ER, remained a separate risk factor. At least two potential mechanisms could explain this phenomenon: the loss of aryl hydrocarbon receptor-mediated antiestrogenic activity or the blockade of a proapoptotic pathway induced by hypoxia. Because several enzymes involved in drug resistance are induced through a xenobiotic response element, the tumors presenting high ARNT splice-variant ratios may be specifically targeted by drugs normally degraded or inactivated. This study shows the biological importance of ARNT splice variants in the behavior of human breast cancer and suggests that the breast cell lines in which the splice variant was discovered may be useful models for further investigation.